Capillary cooling of superconducting coils with two-phase hydrogen or nitrogen. (June 2017) - de Waele, A.T.A.M.; Oswald, B.; Reis, T.; Oswald, J.
Highlights: Matching losses in an AC superconducting motor with the cooling agent. Estimation of the eddy-current heating in the walls of the capillaries. Estimation of the hydrodynamic resistance in the capillaries. Expressions for the temperature distribution inside the coil as function of the AC loss. AC loss as function of the coil temperature and the generated motor power P . Abstract: Superconducting coils in AC application, such as in the stator of superconducting motors, have losses which warm up the coil and so limit the performance. Good thermal contact between the coil and the cooling agent is important. In this research we investigate the possibility of cooling the coils by a cryoliquid, such as liquid hydrogen or liquid nitrogen, flowing through capillaries in thermal contact with the coils.